Achieving market integration : Bbest execution, fragmentation and the free flow of capital - McCleskey, Scott (Oxford ; Burlington : Butterworth-Heinemann, 2004)
This book is a comprehensive and practical explanation of all the interrelated issues surrounding the integration of the securities markets.
Includes bibliographical references (p. 154-156) and index.
aosa13/05/13
Keywords: Securities -- Europe; Money market -- Europe